Modernidade e exclusão em áreas ambientalmente protegidas : olarias e cerâmicas no entorno do Parque Nacional da Serra de Itabaiana - SE - Figueiredo, Carla Taciane (2011)
The theoretical and conceptual maturity, the debate between environmental sciences and late modernity, through discussion of issues relating to the reproduction of socioeconomic disparities en environmental transformations. Thus, this research seeks to answer: The implementation of the National Park of Serra de Itabaiana, as the embodiment of preservation initiative, has contributed to the overcoming of social inequalities in villages Rio das Pedras, World, Gandu I, Gandu II, Lake of the Ovens I and II, the city Itabaiana of Chico Gomes, Areia Branca. What are the economic strategies used by potters and pottery found in the vicinity of Parnassus, to enable their activities? What is the responsiveness of pottery and ceramics to legal requirements arising from implementation of the park? So the objective is to: 1) characterize the economic strategies and capacity of pottery and ceramics of these villages to fulfill legal requirements arising from implementation of Parnassus, 2) identify the possible use of funds from the pottery and ceramics by Parnassus, 3) analyze transformations experienced by these units of production as a result of actions of sustainable development and its possible role in rebuilding social inequalities. To answer the questions and achieve the proposed objectives, we will use the concepts of modernity, environmental conflict and criticism of the notion of sustainable development. This explains the theoretical interconnectivity between different areas of knowledge, predominantly complexity, global and interdisciplinary nature of environmental problems. The investigation of processes of modernization, based on structuration theory, the idea is hypothesized that the creation of Parnassus is configured in the act of entering the region in late modernity in favor of the holders of power, personified in the potters. The methodological approach for the execution of the research is based on qualitative research associated with the ethnographic method. Instruments such as field research, semi-structured interviews with audio recording, document research, were the tools of data collection. The investigation relied on interviews with the owners of the pottery and ceramics and researchers involved in the implementation of Parnassus. Analysis of the interviews was operationalized through the dismemberment of the text, examining the complex variables and phenomena relating to the theory of the structure and concepts of modernity, based on the thematic oral history. Os findings affirm the invisibility of social actors in the institutionalization of the park, This context creates the prerequisite for social and environmental conflicts. The environmental problems that region falls within the overall context of modernity partially excluding the potteries of some modern institutional dimensions.